2010
DOI: 10.3349/ymj.2010.51.5.775
|View full text |Cite
|
Sign up to set email alerts
|

De NovoPericentric Inversion of Chromosome 9 in Congenital Anomaly

Abstract: PurposeThe pericentric inversion of chromosome 9 is one of the most common structural balanced chromosomal variations and has been found in both normal populations and patients with various abnormal phenotypes and diseases. The aim of this study was to re-evaluate the clinical impact of inv(9)(p11q13).Materials and MethodsWe studied the karyotypes of 431 neonates with congenital anomalies at the Pediatric Clinic in Ajou University Hospital between 2004 and 2008 and retrospectively reviewed their clinical data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
0
23
0
4
Order By: Relevance
“…In another study conducted in the Asian population, inv (9) incidence in prenatal group was predicted as 1.2% in Singapore and 1.95% in normal and patient population in Japan as. [7] In a study conducted by Mierla and Stoian with infertile patients, inv (9)-containing karyotype was found in 2.27% of individuals in the patient group and 3.76% in the control group. Although inv (9) was accepted as a minor chromosomal inversion that is not associated with an abnormal phenotype, several studies in the literature have reported contradictory views on its correlation with sterility and subfertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted in the Asian population, inv (9) incidence in prenatal group was predicted as 1.2% in Singapore and 1.95% in normal and patient population in Japan as. [7] In a study conducted by Mierla and Stoian with infertile patients, inv (9)-containing karyotype was found in 2.27% of individuals in the patient group and 3.76% in the control group. Although inv (9) was accepted as a minor chromosomal inversion that is not associated with an abnormal phenotype, several studies in the literature have reported contradictory views on its correlation with sterility and subfertility.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients with inv (9)(p11q13) had various dysmorphic characteristics and/or congenital anomalies. [7] Of the 62 cases with inv (9), 43.5% were couples with habitual abortus, 6.45% were individuals with congenital anomaly, 3.22% were patients with growth deficiency and mental retardation, and 4.83% were patients with gender anomalies. [9] In a study conducted by Dana et al [13] in the Romanian population with 900 infertile couples, inv (9) rate was found to be 3.76%, whereas the same rate was found to be 2.27% in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A chromosomal inversion event was proposed as the genetic mechanism for these observations. Support for this hypothesis was that inversion events were associated in several cases of human Po [Lodder et al, 2009;Jeong et al, 2010]. Similarly, using the mouse, Krebs et al [2003] and Niedermaier et al [2005] induced chromosomal inversions by radiation, which were approximately 1 Mb and 13 kb away from the Shh gene, respectively.…”
Section: Gga2p Inversion Analysismentioning
confidence: 73%
“…Kromozom 1, 9, 16 ve Y'nin heterokromatin bölgelerindeki polimorfizmler sık görülen varyasyonlar olarak bildirilmiştir (1,2). Kromozom 9'un heterokromatin bölgesindeki perisentrik inversiyonu [inv(9)(p11q13)] normal popülasyonda %1-3 oranında bulunan polimorfik bir değişimdir (2). Bu kromozomal değişimin genellikle ailesel geçişli olduğu de novo olguların ise daha nadir görüldüğü bildirilmektedir (3).…”
Section: Introductionunclassified
“…Bu kromozomal değişimin genellikle ailesel geçişli olduğu de novo olguların ise daha nadir görüldüğü bildirilmektedir (3). Genellikle fenotipe yansımayan bu kromozomal değişimin normal bir varyant ya da anormal bir karyotip olup olmadığı kesinlik kazanmamıştır (2,3). Yapılan çalışmalarda infertilite, düşükler, konjenital anomaliler, mental retardasyon, inmemiş testis, gelişme geriliği gibi çeşitli hastalıklarla ilişkisi olabileceği rapor edilmiştir (1-3).…”
Section: Introductionunclassified